Análise da viabilidade do sistema de auditorias de obras públicas do Tribunal de Contas do Estado do Rio de Janeiro à luz do modelo de sistema viável - Brasil, Marconi Canuto (2008)
The Brazilian public administration must act with efficiency, developing its activities with readiness and minimizing the use of resources. However, it has not been being able to work with increasing demand in solve complex problems. Tribunal de Contas do Estado do Rio de Janeiro (TCERJ) is the entity responsible for the operational audit of the public institutions of Rio de Janeiro State and its Municipals districts, except for the Capital. It has detected itself that the society demand is superior to its operational capacity of assistance. This dissertation tries to know if the public works audits system adopted by TCERJ could be considered a viable system. Considering that the systems approaches represents the key to work with a reality more and more complex, the Viable System Modelo (VSM) was adopted as reference, having been developed by Stafford Beer with cybernetics basis. Finally, taking VSM as reference in the normative level, it could be affirmed that the studied system is not a viable system to verify that, the studied system is not a viable system yet.